Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michal; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Erbium-Catalyzed Regioselective Isomerization–Cobalt-Catalyzed Transfer Hydrogenation Sequence for the Synthesis of Anti-Markovnikov Alcohols from Epoxides under Mild Conditions - Liu, Xin; Longwitz, Lars; Spiegelberg, Brian; Tönjes, Jan; Beweries, Torsten; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Charge Distribution in Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes: A Combined X-ray, XAS, XES, DFT, Mössbauer, and Catalysis Approach - Benedikter, Mathis; Musso, Janis; Kesharwani, Manoj K.; Sterz, K. Leonard; Elser, Iris; Ziegler, Felix; Fischer, Felix; Plietker, Bernd; Frey, Wolfgang; Kästner, Johannes; Winkler, Mario; van Slageren, Joris; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Phosphetane Oxides as Redox Cycling Catalysts in the Catalytic Wittig Reaction at Room Temperature - Longwitz, Lars; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Catalytic Approaches to Monomers for Polymers Based on Renewables - Stadler, Bernhard M.; Wulf, Christoph; Werner, Thomas; Tin, Sergey; de Vries, Johannes G. (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions - Longwitz, Lars; Steinbauer, Johannes; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Cocatalyst Designing: A Regenerable Molybdenum-Containing Ternary Cocatalyst System for Efficient Photocatalytic Water Splitting - Busser, G. Wilma; Mei, Bastian; Weide, Philipp; Vesborg, Peter C. K.; Stührenberg, Kai; Bauer, Matthias; Huang, Xing; Willinger, Marc-Georg; Chorkendorff, Ib; Schlögl, Robert; Muhler, Martin (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Formation, Operation and Deactivation of Cr Catalysts in Ethylene Tetramerization Directly Assessed by Operando EPR and XAS - Rabeah, Jabor; Bauer, Matthias; Baumann, Wolfgang; McConnell, Ann E. C.; Gabrielli, William F.; Webb, Paul B.; Selent, Detlef; Brückner, Angelika (ACS Catalysis)
Keywords: Catalysis; General Chemistry